Socialization and Legal Education on Occupational Health and Safety at Assoka Wijaya Workshop, Tabanan - Diah Gayatri Sudibya; Kade Richa Mulyawati (Community Service Journal of Law, 2022)
Universities carry out the Tri Dharma of Higher Education periodically, namely Teaching, Research, and Community Service. In terms of community service activities, there is a sense of caring from campus elements who know directly about the community. The aims of this research are as a form of the Lecturer's dedication to the community, provide opportunities for Lecturers to carry out direct service with partners to the target object, in this case in the Tabanan construction workshop to carry out one of the Tri Dharma Colleges in terms of community service, and improving cooperative relations between universities, the community, and/or companies employing employees.The implementation methods carried out in community service are directly meet partners, discussions with workers and the administration about working time. The result shows that the existence of occupational safety and health regulations which are the operational standards of implementation for the workshop company in Tabanan, after socialization and legal counseling were held, where the company leadership understood and understood the existence of the law governing occupational health and safety and company leaders prepared physical facilities and non-physical company to maintain the safety of its employees. Moreover, if the company leadership does not prepare by the law's mandate, it will be subject to imprisonment or fines. Workers who are not accustomed to using PPE after socialization and legal counseling have been carried out are very understanding and understand that work-related work safety is not only for themselves but also for their families and environment.